Effectiveness of short exposure times to electrolyzed water in reducing Salmonella spp and Imidacloprid in lettuce - Cap, Mariana; Rojas, Dante Emanuel; Fernandez, Mariano Manuel; Fulco, Micaela; Rodriguez, Anabel; Soteras, Trinidad; Cristos, Diego Sebastian; Mozgovoj, Marina Valeria (Elsevier, 2020)
EW has been proposed as a sanitization method for home use to reduce chemical and biological hazards in fresh products. Most studies have evaluated exposure times of 1–10 min which may be too long for processing fresh produce. The aim of this work was to evaluate if short exposure times (15, 30 or 45 s) to electrolyzed water (EW – 50 ppm of free chlorine) were enough to significantly reduce Salmonella spp counts and Imidacloprid concentrations in lettuce. Results showed that EW treatment of 45 s achieved a reduction of 4 log CFU/g in the Salmonella spp counts and a reduction of 48,57% in Imidacloprid concentrations. As to quality parameters, neither texture profile nor flavor were affected by the treatment. The fact that only 45 s were enough to effectively reduced Salmonella spp and Imidacloprid makes the EW treatment an ideal sanitization method for lettuce in both the industry and the household.